Trendovi u zloupotrebi i zloupotrebi pregabalina: 25-godišnja bibliometrijska perspektiva: Bibliometrijska analiza: Pregabalin - AKSUN, SALİHA; KARALAR, Furkan Oguz; Uge, Mert; Cafer, Berna (Journal of Medical Biochemistry, 2025)
AbstractBackground/Aim: Pregabalin, initially developed as an antiepileptic drug, has since been widely used for conditions such as neuropathic pain, generalized anxiety disorder, and fibromyalgia. However, increasing concerns have emerged regarding its misuse and abuse potential, especially among opioid-dependent populations. This study aimed to perform a comprehensive bibliometric analysis to evaluate global research trends, identify prolific contributors, and explore collaborative networks related to pregabalin misuse. Materials and Methods: A bibliometric design was employed using the Web of Science Core Collection database. The search was performed in February 2025, and publications were selected based on predefined criteria. A total of 449 eligible records were analyzed. The bibliometrix R package and its web application, Biblioshiny, within the RStudio environment, were used to conduct statistical and network analyses. Results: Scientific publications addressing pregabalin misuse have markedly increased since 2010. The United States was the most prolific and central actor in global research collaborations, followed by the United Kingdom, Germany, and France. Prominent authors and institutions were found to form tight academic clusters. A steady rise in the usage of keywords such as “abuse,” “addiction,” and “opioids” was observed, particularly after 2016. Conclusion: The growing literature on pregabalin misuse reflects heightened global awareness. Research remains centered in high-income countries, though emerging contributions from developing regions, including Türkiye, are notable. These findings underline the need for interdisciplinary cooperation, informed policy development, and enhanced clinical monitoring to address the risks associated with pregabalin misuse.